What are the Psychological Issuues of Diabetic Ulcer Patients - Kurnia, Anna; Prahastyo, Ade Jundy Fahri; Khoiriyah, Khoiriyah; PS, Dwi Nur Rahmantika (Jurnal Keperawatan Respati Yogyakarta, 2025)
Diabetic ulcers are one of the complications of diabetes mellitus that affect both physical and psychological conditions. The psychological issues that arise include self-motivation, anxiety, self-esteem, and body image. This study to understand the psychological profile of patients with diabetic ulcers. This research uses a quantitative descriptive method. This research was conducted at a wound clinic in the city of Semarang in July – August 2024. The population of this study consists of diabetic ulcer patients receiving treatment at a wound clinic in Semarang City, totaling 55 patients in April 2024. The instruments used in this study include the TSRQ (Treatment Self-Regulation Questionnaire) to assess self-motivation levels, the ZSAS (Zung Self Anxiety Scale) to assess anxiety levels, the RSES (Rosenberg Self Esteem Scale) to assess self-esteem levels, and the body image questionnaire. The results of this study indicate that diabetic ulcer patients have a good level of self-motivation with 12 respondents (21.8%) and a poor level with 43 respondents (78.2%). The level of mild anxiety was reported by 20 respondents (36.4%), moderate by 30 respondents (54.5%), and severe by 5 respondents (9.1%). The level of low self-esteem was reported by 29 respondents (52.7%), moderate by 24 respondents (43.6%), and high by 2 respondents (3.6%). The level of negative body image was reported by 12 respondents (21.8%) and positive by 43 respondents (78.2%). Patients with diabetic ulcers have poor self-motivation, moderate anxiety, low self-esteem, and a positive body image. The suggestion for future researchers is exploring more of the relationship between respondent characteristics and one or more psychological components as factors influencing the healing process of diabetic.